Metabolism of pyruvate and fat - Feigenson, Gerald W. (Henry Stewart Talks, 2020)
Fates of pyruvate, Acetyl-CoA formation, Citric Acid Cycle and connections to other metabolisms, Catabolism of fats, ß-oxidation of fatty acids, Ketone bodies
Reviewed at 2022/11/27